Zygomatic implant penetration to the central portion of orbit: a case report - Luan Mavriqi; Felice Lorusso; Roberto Conte; Biagio Rapone; Antonio Scarano (BMC Ophthalmology, 2021)
Abstract Background Zygomatic implants have been proposed in literature for atrophic maxillary fixed oral rehabilitations. The aim of the present research was to evaluate, by a clinical and tomography assessment, a surgical complication of a zygomatic implant penetration to the orbit. Case presentation A 56 year-old female patient was visited for pain and swelling in the left orbit after a zygomatic implant protocol. The orbit invasion of the zygomatic implant screw was confirmed by the CBCT scan. The patient was treated for surgical implant removal and the peri- and post-operative symptoms were assessed. No neurological complications were reported at the follow-up. The ocular motility and the visual acuity were well maintained. No purulent secretion or inflammatory evidence were reported in the post-operative healing phases. Conclusion The penetration of the orbit during a zygomatic implant positioning is a surgical complication that could compromise the sight and movements of the eye. In the present case report, a zygomatic implant removal resulted in an uneventful healing phase with recovery of the eye functions.